APPLICATION AND EVALUATION OF THE PROPERTIES OF NANOENCAPSULATED PCMS IN TEXTILES - de Lima, Fernando Soares; da Costa, Sirlene Maria; da Costa, Silgia Aparecida; de Oliveira, Adriano Marim (Seven Editora, 2025)
The development of smart fabrics, which actively act in the situations to which they are subjected, has been the subject of research in several industrial areas. Among these materials, textiles containing phase change materials (PCMs) stand out, which act on thermal regulation through the solid-liquid transition, absorbing and releasing heat during this process. This study aimed to select, encapsulate and evaluate the performance of PCMs applied to textiles, aiming at thermal control.Waxes were selected as phase change materials, encapsulated by means of the interfacial polymerization technique, forming microcapsules capable of retaining PCM during thermal cycles. Thermal characterization was performed by differential scanning calorimetry (DSC), while particle morphology and size distribution were analyzed by scanning electron microscopy (SEM) and laser diffraction. Subsequently, the encapsulated PCMs were applied to a flat fabric, being evaluated for thermal conductivity and heat storage capacity through techniques such as infrared thermography and measurement of thermal conductivity and effusivity.The results indicated that textile articles containing encapsulated PCMs had slower heat absorption, greater thermal retention capacity and gradual release of stored heat, when compared to fabrics without PCMs.  The results demonstrate that the incorporation of encapsulated PCMs into fabrics represents a promising strategy for applications where thermal control is desirable, such as functional clothing and technical materials.DOI: https://doi.org/10.56238/sevened2025.021-011